The story of stuff : how our obsession with stuff is trashing the planet, our communities, and our health-- and a vision for change - Leonard, Annie (Free Press, 2010)
This book is based on the author's 2007 internet film, "The Story of stuff." He tracks the life of the "stuff" we use every day, transforming how we think about our patterns of consumption. With just 5 percent of the world's population, [the U.S.] is consuming 30 percent of the world's resources and creating 30 percent of the world's waste--Dust jacket.